Strategi Likuiditas Perbankan Syariah Dalam Menjaga Stabilitas Keuangan - Windi Wulandari; Evelyne Vaquitha; Muhammad Ilham Andika; Putri Nuraini (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Optimal liquidity management is achieved through the optimization of sharia instruments such as Sukuk and Bank Indonesia Sharia Certificates (SBIS) as liquidity buffers, whose effectiveness is significantly moderated by the stability of Third Party Funds (TPF). Furthermore, this strategy is complemented by qualitative managerial practices, such as relationship banking and sharia compliance in handling early withdrawals, as well as the integration of cyber resilience as a liquidity defense against crises of confidence and system disruptions in the digital era. This study aims to analyze and synthesize the most effective sharia banking liquidity strategies in order to maintain financial stability, considering financial, operational, and digital aspects. Using qualitative methods through library research, this study synthesizes findings from various scientific literature on liquidity management, risk, and performance of sharia banks. The results show that liquidity strategies involve a trade-off between profitability and fund security, where strict monitoring of liquidity ratios (Cash Ratio and Current Ratio) serves as an early predictor of financial distress. Keywords: Liquidity Strategy, Islamic Banking, Financial Stability, Islamic Instruments, Cyber ​​Risk. Abstrak Pengelolaan likuiditas yang optimal dicapai melalui optimalisasi instrumen syariah seperti Sukuk dan Sertifikat Bank Indonesia Syariah (SBIS) sebagai penyangga likuiditas, yang efektivitasnya sangat dimoderasi oleh stabilitas Dana Pihak Ketiga (DPK). Selain itu, strategi ini dilengkapi oleh praktik manajerial kualitatif, seperti relationship banking dan kepatuhan syariah dalam penanganan penarikan dana dini, serta integrasi ketahanan siber sebagai pertahanan likuiditas terhadap krisis kepercayaan dan gangguan sistem di era digital. Penelitian ini bertujuan untuk menganalisis dan mensintesis strategi likuiditas perbankan syariah yang paling efektif dalam rangka menjaga stabilitas keuangan, dengan mempertimbangkan aspek finansial, operasional, dan digital. Menggunakan metode kualitatif melalui studi kepustakaan (library research), penelitian ini mensintesis temuan dari berbagai literatur ilmiah mengenai manajemen likuiditas, risiko, dan kinerja bank syariah. Hasil penelitian menunjukkan bahwa strategi likuiditas melibatkan trade off antara profitabilitas dan keamanan dana, di mana pengawasan ketat terhadap rasio likuiditas (Cash Ratio, Current Ratio) berfungsi sebagai prediktor dini financial distress. Kata kunci: Strategi Likuiditas, Perbankan Syariah, Stabilitas Keuangan, Instrumen Syariah, Risiko Siber.